Mobile health applications for supporting self-management of oral systemic anticancer therapy in haematological malignancies: A systematic review of acceptability and efficacy - Lena Mahalingam; Bee Kim Tan; Ping Chong Bee; Chee Hooi Teoh; Renukha Sellappans; Diana Leh Ching Ng; Azlan Husin; Sen Mui Tan; Li-Chia Chen (Digital Health)
Background The acceptability and impact of mobile health (mHealth) applications on health outcomes in haemato-oncology remain unclear, particularly for patients undergoing long-term oral systematic anticancer therapy (SACT). Purpose This systematic review investigated the acceptability and efficacy of mHealth applications in facilitating self-management of oral SACT in patients with haematological malignancies. Methods We conducted a comprehensive search of five electronic databases, PubMed, PsycINFO, CINAHL, Cochrane Library, and Web of Science, until October 2024, and extracted data, including methodologies, application names, functionalities, and key results. This was followed by a narrative synthesis of quantitative outcomes, and a thematic analysis of qualitative data. Results Eight studies were included, comprising three qualitative studies, one randomised controlled trial, one non-randomised trial, and three mixed-method studies. mHealth applications for self-managing oral SACT exhibited acceptability, with usability and satisfaction ratings between 60% and 78%. Using the Normalisation Process Theory, four themes influencing acceptability were: (1) coherence – perceived benefits, (2) cognitive participation – barriers from technical issues, (3) collective action – burden from excessive notifications and inadequate support, and (4) reflexive monitoring – integration challenges in daily routine. Despite no major clinical or behavioural improvements, mHealth applications enhanced patient awareness of support, online health knowledge, and reduced daily life impact. Conclusion Fostering effective self-management of oral SACT in patients with haematological malignancies requires addressing issues such as application glitches, notification fatigue, and integration barriers to optimise these interventions. Future well-designed clinical trials are warranted to validate the impact of these applications on patient outcomes in cancer care.